Honey as Natural Sweetener in Lemon Ready-to-Serve Drink - Sharma, S.; Vaidya, D.; Rana, N. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted to prepare an acceptable ready-to-serve drink by ameliorating honey in lemon juice. Honey a natural sweetener highly nutritious; antioxidant rich and wholesome safe food can be used as substitute for table sugar especially in fruit beverages. Lemon fruit juice a rich source of vitamin C, minerals, carotene and distinct flavor, was utilized along with honey for the preparation of ready-to-serve lemon beverage and was analysed for different physico-chemical characteristics both in raw and processed forms. Honey contains significantly less non-reducing sugars (6.78%) as compared to table sugar (89.41%). The quality of honey can be judged by two indicative parameters i.e. hyrdoxymethyl furfural (HMF) and diastase activity. The hydroxymethylfurfural content recorded in mixed flora honey was 19.36 ppm which was well below the maximum acceptable limits. The quality characteristics of the ready-to-serve drink were evaluated for a period of six months under different storage conditions and showed that honey lemon RTS had significantly higher ascorbic acid content (26.66 mg 100 g-1) and antioxidant activity (27%) than the sugar lemon RTS (ascorbic acid 23.34 mg 100 g-1, antioxidant activity 22%) at fresh stage. Honey lemon RTS awarded with better sensory scores for colour, flavor, taste and overall acceptability over sugar lemon RTS even after storage of six months with minimal changes in its quality characteristics under refrigerated storage and no microbial growth. The natural ready-to-serve beverage made from completely natural ingredients is storage stable and can be commercialized as instant energy drink.